Purification and characterization of laccase from the white-rot fungus Pleurotus pulmonarius VAST02.42 - Dang, Thu Quynh; Le, Viet Hoang; Le, Mai Huong; Do, Huu Nghi (Vietnam Journal of Science and Technology, 2024)
Laccase (EC 1.10.3.2) is a multi-copper oxidase that utilizes molecular oxygen to oxidize phenolic rings to phenyloxy radicals. Due to its capability to use a wide variety of phenolic and non-phenolic substrates, this oxidative enzyme has potential applications in the food, pharmaceutical, and environmental industries. In the present study, a laccase (PleuLac) from the white-rot fungus Pleurotus pulmonarius VAST02.42 that was newly isolated from Muong Phang special-use forest, was purified and studied on physical-chemical properties. After ultrafiltration (10, 30 kDa cut-off), laccase was successfully purified to apparent homogeneity (specific activity of 28 U.mg-1) by using the anion-exchange chromatography (e.g., DEAE-Cellulose, HiTrapTM Q XL columns) and size-exclusion chromatography (Superdex G-100). After the final purification step, a total activity of 532 U was acquired with a recovery of 8.3 % and purity of 9.6-fold. The molecular weight (Mw) of PleuLac was determined to be 35 kDa by SDS-PAGE electrophoresis. This enzyme exhibited an optimal activity at 40 ºC and pH of 5.5; it is stable at 25 ºC after incubation of 120 min and pH of 5.0. This purified and characterized PleuLac will serve for further application study on catalyzing the oxidation of essential oils to value-added products in combination with peroxidase.